Influence of carboxylated multi-walled carbon nanotube on the thermostability, and viscoelastic properties of poly (ether imide)/carbon fiber laminates - de Paula Santos, Luis Felipe [UNESP]; Moraes, Carlos Eduardo [UNESP]; do Amaral, Tamires Repullio [UNESP]; da Silva Silveira, Mauro Ricardo; Ferreira, Carlos Arthur; Ribeiro, Bruno [UNESP]; Costa, Michelle Leali [UNESP]; Botelho, Edson Cocchieri [UNESP] (Elsevier, 2022)
Carbon nanotubes have boosted research in several areas, especially in nanostructured thermoplastic composites. This work comes as its most significant contribution, the processing, and evaluation of the influence of the multi-walled carbon nanotubes (MWCNT) content on the viscoelastic, thermal stability, and flammability behavior of poly (ether imide) (PEI)/carbon fiber laminates. MWCNT favored an increase in composites' thermal stability, however, the pyrolysis temperature was not influenced by MWCNTs, and a reduction in pHRR (peak of heat release rate) and THR (total heat release) were observed. From DMA, despite the reduction in glass transition temperature (Tg), there was an increase of the storage modulus, an increase in the interphase region, and a more outstanding contribution to the viscoelastic properties from the MWCNT addition. TTS analysis also showed an enhancement of long-term stability when carbon nanotubes were added.
Keywords: Inflammability properties; Multi-walled carbon nanotube; Thermal stability; Thermoplastic composites; Viscoelastic properties